Corps à corps en 2007 : Nicolas Sarkozy face à Ségolène Royal - Hugues de Chanay (Itinéraires)
This article aims to assess how fondamental a role the body, viewed in an interactive and multimodal perspective, plays (through gestures, postures, mimics, and glances) in the construction of positions of enunciation and discursive identities (ethos) in political media debates and specifically the May 2007 debate berween Nicolas Sarkozy (NS) and Ségolène Royal (SR). NS can physically compose a somatic image of himself, demonstrating in action his capacity to unite his diverse audience—a definite edge in the context of a presidential election—in contrast with SR, who appears more as an activist whose discourse seems geared toward her own traditional electorate. The body is both an instrument used to “write,” spatially and dynamically, identities in the ongoing interaction, as well as the raw material, so to speak, and the médium for durably writing the very identities it contributes to define.